Bediuzzaman Said Nursi - Akhmetova, Elmira (2017)
This presentation talks about the life, works, and ideas of a Turkish scholar, Bediuzzaman Said Nursi. It focuses on his ideas on secularism, extremism, nationalism and Muslim unity.